ChemInform Abstract: Nicotinic Acetylcholine Receptor Agonists: A Milestone for Modern Crop Protection. Issue 48 (26th November 2013) - Jeschke, Peter; Nauen, Ralf; Beck, Michael Edmund
Abstract Review: 99 refs.